Exploring Gamification Strategy for Developing MSMEs during the COVID-19 Pandemic - Arief Dwi Saputra; Alfina Rahmatia; Sri Handari Wahyuningsih; Andi Azhar (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
The COVID-19 pandemic brought about employees to be less enthusiastic due to the declining competitiveness and switching systems from offline to online. This study closely scrutinized how gamification strategies assume a part in entrepreneurial behavior on attitudes, subjective norms and behavioral control, and entrepreneurial education through self-efficacy, experience, and program involvement. Purposive sampling was utilized to choose a sample of 442 informants for this qualitative study. The review was carried out through a literature study and reinforced by in-depth interviews. The data was coded using the Nvivo 12 application with word similarity analysis at a maximum percentage of 100%. Based on the results of word similarity, there was a similarity in the relationship related to cluster analysis which classified the mutually supportive roles among variables as a business strategy during the pandemic. Overall, the application of gamification displays an impact on motivation, behavior change, and psychological effects on entrepreneurial behavior and education. The research contribution is utilized to address issues in the role of the organization as a solution to the relationship between gamification strategies and employee performance. The application of gamification strategies plays a role in opening fascinating exploration in the future. Further studies are expected to discuss pertaining business strategies in dealing with unexpected moments such as the COVID-19 pandemic.